2009
DOI: 10.1029/2008rs004035
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and simulation of ionospheric scattering on VHF and UHF radar signals: Coherence times, coherence bandwidths, and S4

Abstract: [1] Irregularities in the electron density of the ionosphere cause phase and amplitude scintillation on transionospheric VHF and UHF radar signals, particularly at lower radio frequencies. The design of radar and other transionospheric systems requires good estimates of the coherence bandwidth (CB) and coherence time (CT) imposed by a turbulent ionosphere. CB and CT measurements of the equatorial ionosphere, made using the Advanced Research Project Agency Long-range Tracking and Identification Radar 158 MHz an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The coherence of signals can be seriously affected by scintillation [22], [23], which can reduce the resolution of SAR imaging. Previous papers about its effects on SAR imaging are studied in detail; an analytical study is proposed by Ishimaru et al [7] and also studied by others [24]- [28].…”
Section: Effects Of Ionospheric Scintillation On Sar Imagementioning
confidence: 99%
“…The coherence of signals can be seriously affected by scintillation [22], [23], which can reduce the resolution of SAR imaging. Previous papers about its effects on SAR imaging are studied in detail; an analytical study is proposed by Ishimaru et al [7] and also studied by others [24]- [28].…”
Section: Effects Of Ionospheric Scintillation On Sar Imagementioning
confidence: 99%
“…We assume three active targets (I=3 and i=0,1,2), and the basic frequency of each dual-tone signal is f 0 =1 MHz, f 1 =1.1 MHz, f 2 =1.2 MHz. The frequency difference g b =50 kHz, which is smaller than the typical channel coherence bandwidth at the VHF band [22]. The directly sampling frequency f s =3 MHz.…”
Section: Simulation and Resultsmentioning
confidence: 97%
“…As soon as more measurements are collected in different configurations, the dependence of this relation with location, hour, season, and sunspot number can be checked. Cross‐evaluation against phase screen model simulations [ Rogers et al , 2009a, 2009b] or theoretical calculations [ Rino , 1979] will also likely provide further insights into this relationship. This is likely to be the subject of a later paper.…”
Section: Extension To Longer Distancesmentioning
confidence: 99%
“…In a previous study it was found that in equatorial regions, decorrelation of a SAR due to ionospheric scintillation is likely to occur for ∼40% of the time in the evening hours between 1800 and 2400 LT at sunspot maximum [ van de Kamp et al , 2009]. In other recent studies, measurements using the ALTAIR radar on Kwajalein Atoll and associated modeling using the Trans‐Ionospheric Radio Propagation Simulator (TIRPS) have quantified the coherency bandwidth and coherency time of VHF and UHF signals propagating through the equatorial ionosphere [ Cannon et al , 2006; Rogers et al , 2009a, 2009b].…”
Section: Introductionmentioning
confidence: 99%